Tverrfaglig forskningsstøtte - et FagSosioTeknisk grenseobjekt - Ebeltoft, Nini; Lykkja, Pål Magnus; Hegnes, Alte Wehn (Nordisk Tidsskrift for Informationsvidenskab og Kulturformidling, 2018)
It is widely acknowledged that interdisciplinary research is required for adequately addressing global challenges. This article explores what interdisciplinary research implies for research libraries assisting such work, and for researchers receiving support. The main research question is: In what manner is interdisciplinary research support shaped and constructed as a result of contact and collaboration between researchers and the research library? Along with document studies, 15 semi-structured interviews have been conducted involving academic staff at the University of Oslo (UiO) and librarians at the UiO research library. Theoretical insight from the fields of Library and Information Science and Science and Technology Studies are combined using Boundary Objects (BO) as an analytical concept. In analysing empirical data, two dual-level competencies and library practices are identified: those that are technical and librarian, and those that are academically-professional and socio-emotional. In the junctions between these, interdisciplinary research support appears as a boundary object characterized as SubjectSocioTechnical. Collaboration and support for interdisciplinary research call for a complex of competencies, primarily because various support practices must be tailored to fit researchers’ disciplines and needs.